2019
DOI: 10.1016/j.jceh.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Normal Values of Serum Aminotransferases in Healthy Indian Males

Abstract: Background: The normal range for Aspartate and Alanine Aminotransferases (AST and ALT) levels (<40 [ 2 0 6 _ T D $ D I F F ] IU/L) were set in 1950s. Recent data from certain countries suggest lower levels of AST and ALT. Aim of the study was to redefine the normal values of aminotransferases in healthy Indian adults. Methodology: In a cross sectional prospective study, 1002 blood donors were evaluated to isolate a healthy cohort. Four and 9 subjects positive for HBsAg and anti-Hepatitis C Virus (HCV) respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[28][29][30] In fact, a recent ultrasound-based study in healthy blood donors of Chandigarh found that 528 out of 986 (53.5%) donors had NAFLD, and at least one component of metabolic syndrome was present in 96% (506 of 528) of subjects with NAFLD. 31 We published our experience of liver donor liver biopsies; 50.4% of apparently healthy prospective liver donors had NAFL. 32 NAFLD contributes significantly to liver disease-related morbidity in India 33 and has a different clinicopathological profile from West.…”
Section: Indians Are At More Risk Of Cvdmentioning
confidence: 99%
“…[28][29][30] In fact, a recent ultrasound-based study in healthy blood donors of Chandigarh found that 528 out of 986 (53.5%) donors had NAFLD, and at least one component of metabolic syndrome was present in 96% (506 of 528) of subjects with NAFLD. 31 We published our experience of liver donor liver biopsies; 50.4% of apparently healthy prospective liver donors had NAFL. 32 NAFLD contributes significantly to liver disease-related morbidity in India 33 and has a different clinicopathological profile from West.…”
Section: Indians Are At More Risk Of Cvdmentioning
confidence: 99%